Global trends in metacognition research for mathematics learning: A systematic literature review - Viona Yuliza; Rohati Rohati; Duano Sapta Nusantara (Jurnal Elemen, 2026)
Although metacognition plays a pivotal role in mathematics learning, comprehensive studies mapping the global research landscape over the past five years remain scarce. This study addresses this gap by systematically examining global metacognitive research in mathematics education from 2021 to 2025. A systematic literature review (SLR) integrated with bibliometric analysis was conducted on 29 studies retrieved from six scientific databases (Scopus, ScienceDirect, PubMed, ERIC, Springer, and IEEE Xplore), following PRISMA 2020 guidelines. Two independent reviewers conducted screening; disagreements were resolved through discussion. Bibliometric visualization was performed using VOSviewer 1.6.20. Four main findings emerged: (1) research trends reveal theoretical maturity from basic studies toward cognitive-affective integration and technology-enhanced interventions; (2) Turkey and Indonesia lead research productivity (14% each), with Asian countries accounting for 55% of total output; (3) methodological approaches are balanced across qualitative, quantitative, and mixed-methods designs; and (4) metacognitive awareness significantly predicts mathematics achievement, operates within an integrated cognitive-affective system, shows individual differences, and is trainable through interventions, yet low-achieving students exhibit calibration problems. This study lays the groundwork for designing evidence-based metacognitive interventions and informing future research directions in mathematics education. Researchers and curriculum designers are encouraged to prioritize longitudinal designs, valid assessment instruments, and technology integration.